2022
DOI: 10.1161/cir.0000000000001040
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Management of Cardiovascular Risk Factors for Adults With Type 2 Diabetes: A Scientific Statement From the American Heart Association

Abstract: Cardiovascular disease remains the leading cause of death in patients with diabetes. Cardiovascular disease in diabetes is multifactorial, and control of the cardiovascular risk factors leads to substantial reductions in cardiovascular events. The 2015 American Heart Association and American Diabetes Association scientific statement, “Update on Prevention of Cardiovascular Disease in Adults With Type 2 Diabetes Mellitus in Light of Recent Evidence,” highlighted the importance of modifying various risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
194
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 271 publications
(254 citation statements)
references
References 331 publications
(455 reference statements)
1
194
0
8
Order By: Relevance
“…Why is there such a large gap? Although, SGLT-2i with GLP-1 RAs in diabetic patients, especially those with ASCVD, are recommended by several guidelines ( 2 – 6 ), they are expensive and many patients, especially those without medical insurance, are restricted. Moreover, since China is currently implementing a Diagnosis Related Groups (DRG) payment policy, the conditions for medical insurance reimbursement for the use of GLP-1RAs or SGLT-2i are relatively strict, which also greatly limits the use in patients with medical insurance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why is there such a large gap? Although, SGLT-2i with GLP-1 RAs in diabetic patients, especially those with ASCVD, are recommended by several guidelines ( 2 – 6 ), they are expensive and many patients, especially those without medical insurance, are restricted. Moreover, since China is currently implementing a Diagnosis Related Groups (DRG) payment policy, the conditions for medical insurance reimbursement for the use of GLP-1RAs or SGLT-2i are relatively strict, which also greatly limits the use in patients with medical insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerotic cardiovascular disease (ASCVD)-defined as coronary heart disease (CHD), cerebrovascular disease, or peripheral arterial disease presumed to be of atherosclerotic origin-is the leading cause of morbidity and mortality in individuals with diabetes ( 2 – 4 ). Glycemic control alone has a limited role in reducing the risk of ASCVD and the integrated management of multiple risk factors such as glycemia, blood pressure, lipids, and obesity, as well as the combination of appropriate antiplatelet therapy is crucial to minimize the risk of cardiovascular events and mortality ( 3 , 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different scientific societies recommend the use of antidiabetic therapies in CVD, including the AHA [ 39 ], the ADA [ 91 ], the ESC [ 41 ] and the ESC/EASD [ 40 ]; Chinese scientific bodies, however, do not [ 92 ]. The overall medication regimen is roughly similar, with a key focus on metformin, GLP-1 agonists and SGLT2 inhibitors in guidelines for treating CVD in T2DM patients (Table 5 ).…”
Section: Current Recommendations On the Use Of Antidiabetic Drugs Wit...mentioning
confidence: 99%
“…The presence of hypertension in patients with T2DM significantly increases the risk of CVD development, and a study revealed that evaluated blood pressure down to < 120 mm Hg and < 70 mm Hg could decrease mortality, macrovascular, and microvascular events regardless of baseline systolic blood pressure [ 39 ]. Thus, lowering blood pressure reduces CVD events and microvascular complications and has a favorable effect on CVD outcomes in patients with and without T2DM.…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation